Momentum and Informed Trading - Hameed, A. (Institutional Knowledge at Singapore Management University, 2008)
Consistent with the predictions of Wang (1994), we document that firm-specific informed trading is an important determinant of price momentum. The stronger return continuation in stocks with more informed trading cannot be explained by cross-sectional differences in uncertainty proxies such as analyst forecast dispersion, analyst coverage, idiosyncratic return volatility, and size. The relationship between informed trading and return continuation is also not attributable to cross-sectional differences in liquidity. Instead, our evidence emphasizes the role of price discovery in generating short-term price momentum.